Amplified environmental change: Evidence from land‐use and climate change in medieval Minorca. (16th January 2018) - Balbo, Andrea Luca; Puy, Arnald; Frigola, Jaime; Retamero, Felix; Cacho, Isabel; Kirchner, Helena
Abstract: The debate on human environmental impact has often been locked into cause–effect reasoning, aiming at factoring human impact on top of climatic variability. Here we use evidence from Minorca and the Mediterranean region to show the potential for amplified environmental change emerging from complex feedbacks between climatic and historical events. Alluvial sediments collected in a gully reveal a 14‐ to 27‐fold increase in sediment accumulation rates, leading to the rapid aggradation of the valley floor from approximatelyad 1300 onwards. These environmental changes coincided with the Feudal conquest of Minorca (ad 1287) and with the climatic shift from the Medieval Climate Anomaly (MCA, c.ad 900–1300) to the Little Ice Age (LIA, c.ad 1300–1850). This evidence of unprecedented sediment mobilisation, in context with climatic and historical events marking the Mediterranean region, highlights the implications for environmental vulnerability emerging from positive feedbacks between climate and land‐use. Understanding such interactions in historical contexts is paramount to increase our capacity for anticipatory learning in the face of rapid climatic, economical, and ecological transformations today.